2004
DOI: 10.1063/1.1789237
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of nitrogen incorporation in GaAsN alloys

Abstract: We have investigated nitrogen incorporation mechanisms in dilute nitride GaAsN alloys grown by plasma-assisted molecular-beam epitaxy. A comparison of nuclear reaction analysis and Rutherford backscattering spectrometry in channeling and nonchanneling conditions reveals significant composition-dependent incorporation of N into nonsubstitutional sites, presumably as either N -N or N -As split interstitials. Furthermore, we identify the ͑2 ϫ 1͒ reconstruction as the surface structure which leads to the highest s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…The difference in the structures of GaAs and GaN and the large difference in the sizes of arsenic and nitrogen do not allow the formation of complete range of solid solution in this alloy. The smaller size of N allows its solubility in GaAs and extensive research has been reported on such alloys [3][4][5][6][7][8]. In comparison, owing to the larger size of As and consequent difficulty in the incorporation of As in GaN, very limited work has been reported on N-rich side of GaAs x N 1−x alloys, which have been mostly prepared by MOCVD and MBE [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The difference in the structures of GaAs and GaN and the large difference in the sizes of arsenic and nitrogen do not allow the formation of complete range of solid solution in this alloy. The smaller size of N allows its solubility in GaAs and extensive research has been reported on such alloys [3][4][5][6][7][8]. In comparison, owing to the larger size of As and consequent difficulty in the incorporation of As in GaN, very limited work has been reported on N-rich side of GaAs x N 1−x alloys, which have been mostly prepared by MOCVD and MBE [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the existence of N-N split interstitials, N-As split interstitials, or (AsGa-NAs) nn pairs in Ga(AsN) has been suggested theoretically [79] and verified experimentally [80,81]. Also, the low solubility of N in GaAs [82] has been reported to induce the clustering of N atoms [83] in the alloy.…”
Section: Analysis Of the N Distribution In Gaasnmentioning
confidence: 99%
“…12 As nitrogen is sensitive to nuclear reaction analysis (NRA), channeling NRA provided direct experimental evidence for the identification of such interstitial nitrogen. [13][14][15][16][17] Further study also revealed that the decrease of the interstitial N concentration induced by rapid thermal annealing could result in an increase in carrier concentration and mobility. 18 Compared with N-doped III-V HMAs, there is much poorer understanding of oxygen incorporation in II-VI alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial efforts have been made to investigate the location of nitrogen dopant in GaAsN HMAs. [12][13][14][15][16][17] In addition to substitutional placement, a considerable fraction of the nitrogen might present as N-N or N-As split interstitials. 12 As nitrogen is sensitive to nuclear reaction analysis (NRA), channeling NRA provided direct experimental evidence for the identification of such interstitial nitrogen.…”
Section: Introductionmentioning
confidence: 99%